Optimizing bone transport strategies: a pixel value ratio-based evaluation of regeneration rates in bifocal and trifocal techniques - Yang, Xin; Hamiti, Yimurang; Liu, Kai; Wang, Sulong; Kadier, Xiriaili; Xiong, Debin; Yusufu, Aihemaitijiang (Frontiers in Surgery, 2024)
BackgroundBone transport techniques are crucial for managing large bone defects, but the optimal approach for different defect lengths remains unclear. This study aimed to compare bone regeneration rates between short bifocal bone transport (SBBT), long bifocal bone transport (LBBT), and trifocal bone transport (TBT) using pixel value ratio (PVR) as an objective quantitative measure.MethodsThis retrospective study included 60 patients undergoing lower limb bone transport, divided into SBBT (n = 22, defects <6 cm), LBBT (n = 20, defects ≥6 cm), and TBT (n = 18, defects ≥6 cm) groups. PVR was measured at 4, 8, and 12 weeks postoperatively using standardized digital radiographs. Healing index (HI) and external fixation index (EFI) were calculated to assess treatment efficiency. Demographic data, surgical characteristics, and complications were also analyzed.ResultsTBT showed significantly higher PVR values compared to LBBT at all time points (4 weeks: 0.779 ± 0.036 vs. 0.719 ± 0.027, p < 0.001; 8 weeks: 0.822 ± 0.027 vs. 0.787 ± 0.025, p = 0.008; 12 weeks: 0.866 ± 0.024 vs. 0.835 ± 0.016, p = 0.023) and to SBBT at 4 and 8 weeks (p < 0.001 and p = 0.016, respectively). The TBT group demonstrated significantly lower HI and EFI compared to both SBBT and LBBT groups (p < 0.05), indicating faster healing and shorter treatment times. Although SBBT showed slightly higher PVR values than LBBT, the differences were not statistically significant.ConclusionTrifocal bone transport leads to faster bone regeneration and shorter treatment times compared to bifocal techniques, particularly for longer bone defects. The study demonstrates that defect length alone may not be the primary factor influencing regeneration rates in bifocal transport. PVR proves to be a reliable and cost-effective tool for assessing bone regeneration in different bone transport techniques, offering potential for guiding clinical decision-making. These findings suggest that trifocal transport should be considered as a preferred method for treating larger bone defects, especially when minimizing treatment time is crucial.